Here it is : a tribute to Leonard Cohen [compact disc]. - Cohen, Leonard, 1934-2016 (Blue Note, 2022)
Producer Larry Klein pays tribute to his dear friend Leonard Cohen with an album that presents stunning new renditions of the legendary singer-songwriter's compositions performed by an extraordinary line-up of vocalists: Norah Jones, Peter Gabriel, Gregory Porter, Sarah McLachlan, James Taylor, Iggy Pop, and Mavis Staples. The album's twelve tracks offer a broad range of Cohen's songs drawn from his 1967 debut Songs of Leonard Cohen through his final album, You Want It Darker; released just days before his death in 2016. The set covers some of his best-known classics ("Hallelujah," "Suzanne") and less familiar deep cuts.